Pharmacological treatment of the biochemical defect in cystic fibrosis airways - Rodgers, H C; Knox, A J (The European respiratory journal, 2001)
The understanding of the biochemical defect in cystic fibrosis (CF) has advanced considerably since discovery of the CF gene in 1989 and characterization of its product. Studies showing that the abnormality in chloride flux could be corrected by transfection of wild-type cystic fibrosis transmembrane conductance regulator (CFTR) complimentary deoxyribonucleic acid (cDNA) have led to gene therapy trials on both sides of the Atlantic. However, gene therapy as a treatment for CF has yet to be realized. Pharmacological manipulation of the biochemical defect may provide an alternative or complementary approach to treatment. This review will discuss pharmacological agents in development which could correct the abnormal ion movement. The mechanisms of action of these pharmacological agents can be divided broadly into drugs which affect the most common CF mutation, deltaF508, which increase trafficking of the mutant CF protein to the apical membrane; drugs which increase chloride secretion; and drugs which reduce sodium reabsorption across the apical membrane. Treatment options for cystic fibrosis have developed rapidly since discovery of the cystic fibrosis gene over a decade ago. The targeting of specific therapies for particular cystic fibrosis genotypes and the use of combination treatments of chloride channel openers with sodium channel blockers are likely to be key advances in the next decade.